Motivation to Learning Mathematics and Gender as Correlates of Senior Secondary School Students’ Performance in Mathematics - Adeneye O. A. Awofala; Abisola O. Lawani; Olayinka A. Adeyemi (Universitas Riau, 2020)
This study investigated senior secondary school students’ motivation to learning mathematics and gender as correlates of performance in mathematics. The sample consisted of 315 students from two government senior secondary schools in Lagos State, Nigeria using the quantitative research method within the blueprint of the descriptive survey research design. Data collected were analysed using percentages, means, standard deviation, independent samples t-test, Pearson Product Moment Correlation Coefficient (PPMCC) and standard and stepwise multiple linear regression analysis. Findings from the study revealed that there was a very high level of motivation to learn mathematics among senior secondary schools’ students in Nigeria. There was a significant influence of gender on students’ performance in mathematics but not on motivation to learn mathematics. It was also revealed that self-efficacy, gender and intrinsic motivation were the major significant predictors of performance in mathematics among the sample studied. Based on these findings, future studies in Nigeria should attempt to investigate the psychometric properties of the motivation to learn mathematics scale.